Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
(x+4)²= (x+4)×(x+4)
Use the FOIL method to simplify
F=First (multiply the first number of each expression)
O=Outside (multiply the outside edges of each expression)
I= Inside (multiply the inside edges of each expression)
L= Last (multiply the last number of each expression)
x times x= x²
x times 4= 4x
4 times x= 4x
4 times 4= 16
Add them together, we have: x²+4x+4x+16
We can simplify this by adding like terms
4x+4x=8x
Final expression= x² + 8x + 16
Use the FOIL method to simplify
F=First (multiply the first number of each expression)
O=Outside (multiply the outside edges of each expression)
I= Inside (multiply the inside edges of each expression)
L= Last (multiply the last number of each expression)
x times x= x²
x times 4= 4x
4 times x= 4x
4 times 4= 16
Add them together, we have: x²+4x+4x+16
We can simplify this by adding like terms
4x+4x=8x
Final expression= x² + 8x + 16
[tex](x+4)^2 = x^2 + 2(x)(4) + 4^2 .....................(By-identity) \\ \\ => x^2 + 8x + 16[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.